An Asynchronous FPGA Block with Its Tech-Mapping Algorithm Dedicated to Security Applications. (5th January 2013) - Beyrouthy, Taha; Fesquet, Laurent
Abstract : This paper presents an FPGA tech-mapping algorithm dedicated to security applications. The objective is to implement—on a full-custom asynchronous FPGA—secured functions that need to be robust against side-channel attacks (SCAs). The paper briefly describes the architecture of this FPGA that has been designed and prototyped in CMOS 65 nm to target various styles of asynchronous logic including 2-phase and 4-phase communication protocols and 1-of- n data encoding. This programmable architecture is designed to be electrically balanced in order to fit the security requirements. It allows fair comparisons between different styles of asynchronous implementations. In order to illustrate the FPGA flexibility and security, a case study has been implemented in 2-phase and 4-phase Quasi-Delay-Insensitive (QDI) logic.